(untitled) (Texas Journal of Philology, Culture and History, 2022)
This article emphasizes the importance of developing the philosophy of education in raising the worldview, consciousness and thinking of a person. The article also analyzes the impact of innovations in the education system on the development of society through the ideas set forth in the works of the educator A. Fitrat.